2013
DOI: 10.1074/jbc.m112.442905
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin-2 Is Required to Control Proton Leak through Uncoupling Protein-3

Abstract: Background: Glutaredoxin-2 (Grx2) modulates reversible glutathionylation of mitochondrial proteins. Results: Grx2 glutathionylates and inhibits UCP3-mediated proton leak. Conclusion: Grx2 modulates UCP3 activity. Significance: Grx2 is required to control proton leak through UCP3 and mitochondrial metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 65 publications
4
88
1
Order By: Relevance
“…Previous studies have indicated that Grx2 is a key regulator of redox homeostasis in the mitochondria, and it controls complex I activity in the electron transport system (ETS) for oxygen reduction and ATP production (37,38). The results in this study as shown in Figs.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have indicated that Grx2 is a key regulator of redox homeostasis in the mitochondria, and it controls complex I activity in the electron transport system (ETS) for oxygen reduction and ATP production (37,38). The results in this study as shown in Figs.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the AOX, uncoupling protein (UCP), and several peptides associated with the mitochondrial electron transport chain, alongside Gly decarboxylase, Ser hydroxymethyltransferase, several amino transferases, and enzymes of branched chain amino acid metabolism, were also identified as putative targets (13,19,22). Notably, in nonplant systems, other enzymes associated with the mitochondrial electron transport chain (e.g., complex II, UCP) have been identified as being redox-regulated (48,49). Here, we adopted .…”
Section: Discussionmentioning
confidence: 99%
“…S-glutathionylation of UCP3 was also discovered to be catalyzed by the enzyme GRX2 (Mailloux et al, 2013). In GRX2 knock out mice, UCP3 was less glutathionylated which resulted in increased state 4 respiration (Mailloux et al, 2013). UCP2 has also been found to be S-glutathionylated, which was shown to play a part in regulating glucose-stimulated insulin release (Mailloux et al, 2012a,b).…”
Section: Uncoupling Proteins-2 Andmentioning
confidence: 99%
“…S-glutathionylation of UCP3 causes a decrease in state 4 respiration in primary cells and skeletal muscle mitochondria . S-glutathionylation of UCP3 was also discovered to be catalyzed by the enzyme GRX2 (Mailloux et al, 2013). In GRX2 knock out mice, UCP3 was less glutathionylated which resulted in increased state 4 respiration (Mailloux et al, 2013).…”
Section: Uncoupling Proteins-2 Andmentioning
confidence: 99%